Histomorfometria da inervação proprioceptiva faríngea na apneia obstrutiva do sono: estudo caso-controle - Dantas, Guilherme Leal (2023)
Obstructive Sleep Apnea is a disorder characterized by recurrent collapses of the pharynx during sleep, resulting in reduced oxygen saturation and a high risk of cardiovascular diseases. The lateral pharyngeal walls play a crucial role in the collapse of the upper airway during apneic episodes. The pathophysiological mechanism still remains uncertain. Evidence suggests that changes in proprioceptive sensory innervations of the pharynx may contribute to the development of the disease. The main objective of this study is to investigate the qualitative and quantitative sensory innervation of the palatoglossus, palatopharyngeus, and superior pharyngeal constrictor muscles in a control group with normal sensory function and no obstructive sleep apnea, and a group of apneic patients. The specimens were collected in vivo through tonsillectomy in the control group and lateral pharyngoplasty in the case group. Histomorphometry of nerve endings was assessed using hematoxylin-eosin staining and immunofluorescence methods. In the control group, muscle spindles were visualized in the palatoglossus muscle, and free, complex nerve endings were identified in all three muscles, including Meissner, Golgi, and Ruffini-like formations, as well as spiral-wharves nerve structures in the palatoglossus and superior pharyngeal constrictor muscles. In the case group, morphological abnormalities were observed in the sensory corpuscles, with a high prevalence of unclassifiable complex nerve formations, and a reduction in the perivascular plexus. Spiral-wharves nerve formations were observed in all muscles of the apneic patients. Superior pharyngeal constrictor muscle was the most affected in the case group, showing a lower variety of nerve formations. There was a decrease in nerve fiber density in the palatopharyngeus and superior pharyngeal constrictor muscles of the case group compared to the control. There was a strong and directly proportional correlation between the nerve density of the palatopharyngeus muscle and the nadir of oxyhemoglobin saturation. The nerve density of the superior pharyngeal constrictor muscle showed an inversely proportional correlation with the apnea-hypopnea index and the percentage of total sleep time with oxyhemoglobin saturation below 90%. The study of pharyngeal proprioceptive sensory innervation expands the understanding of pathophysiology, aids in determining severity factors and prognosis of obstructive sleep apnea and may influence therapeutic selection and the development of new pharmacological therapies.